Studies on Haemato- Biochemical Changes and Evaluation of Combination Therapy Against B. gibsoni - Yadav, Narayani; Mondal, Debabrata; Raguvaran, R.; Das, Arvind Kumar; Sharma, Dushyant Kumar; Saxena, Abhishek Chandra (International Journal of Livestock Research, 2021)
Babesiosis is one of the main causes of anemia in dogs and lot of research has been proposed for its pathogenesis. Present study was envisaged to study the hemato-biochemical changes with different therapeutic interventions against Babesia gibsoni in canines. During the study period, 2236 dogs were presented to TVCC, IVRI, of which 48 dogs were suspected for hemoprotozoan diseases and finally 15 dogs were found positive for B. gibsoni by microscopic examination. Blood samples were taken to study hematological and serum changes. Positive dogs were randomly divided into 3 groups (n=5) for different therapeutic interventions. Dogs of Gr. I received Berenil (5mg/Kg IM) and was repeated after 7 days. Dogs of Gr. II were treated with combination of Doxycycline @ 10mg/Kg PO q12h and Clindamycin @ 25mg/Kg q12h for 21 days. Dogs of Gr. III received combination of Doxycycline @ 10mg/Kg q12h, Clindamycin @25mg/Kg q12h, Metronidazole @ 7mg/Kg q12h for 21 days. All the treated dogs received need based supportive therapy in addition to the specific therapy.